The Effect of Addition of SnO2 Doping on The Electronic Structure of TiO2 Thin Film as Photo-Anode in DSSC Applications - Soni Prayogi; Marza Ikhsan Marzuki (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2022)
Photoanode is a component of the dye-sensitized solar cell (DSSCc) which is synthesized from metal oxide semiconductor material with nanoparticle size deposited on transparent conductive glass. TiO2 powder was synthesized by mixing 20 mL of Titanium (III) chloride (TiCl3) with 100 mL of the equator and stirred for 1 hour. TiO2-SnO2 thin films have been successfully synthesized using the coprecipitation method and coated on ITO (Indium Tin Oxide) substrate by doctor-blade technique. The structure and morphology of the films were investigated by XRD and SEM respectively. The analysis of optical characteristics shows that the absorbance of TiO2 photoanode is in the wavelength range of 300-600 nm while SnO2 is in the wavelength range of 300-870 nm. The results showed that the synthesized film with SnO2 had a stronger anatase formation than the film with pure TiO2. Finally, incorporating SnO2 into the TiO2 matrix is an effective strategy to improve the overall properties of solar cells in future applications